Azimuthal anisotropy of magnetic fields in the circumgalactic medium driven by galactic feedback processes - Ramesh, Rahul; Nelson, Dylan; Heesen, Volker; Brüggen, Marcus (Monthly notices of the Royal Astronomical Society, 2023)
We use the TNG50 cosmological magnetohydrodynamical simulation of the IllustrisTNG project to show that magnetic fields in the circumgalactic medium (CGM) have significant angular structure. This azimuthal anisotropy at fixed distance is driven by galactic feedback processes that launch strong outflows into the halo, preferentially along the minor axes of galaxies. These feedback-driven outflows entrain strong magnetic fields from the interstellar medium, dragging fields originally amplified by small-scale dynamos into the CGM. At the virial radius, z = 0 galaxies with M⋆ ∼ $10^{10}\, \rm {M_\odot }$ show the strongest anisotropy (∼0.35 dex). This signal weakens with decreasing impact parameter, and is also present but weaker for lower mass as well as higher mass galaxies. Creating mock Faraday rotation measure (RM) sightlines through the simulated volume, we find that the angular RM trend is qualitatively consistent with recent observational measurements. We show that rich structure is present in the circumgalactic magnetic fields of galaxies. However, TNG50 predicts small RM amplitudes in the CGM that make detection difficult as a result of other contributions along the line of sight.